2021
DOI: 10.1101/2021.06.29.21259609
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neuropsychiatric disorders as risk factors and consequences of COVID-19: A Mendelian randomization study

Abstract: Background More than 170 million cases of COVID-19 have been reported worldwide. It has been proposed that psychiatric disorders may be risk factors and/or consequences of COVID-19 infection. However, observational studies could be affected by confounding bias. Methods We performed bi-directional two-sample Mendelian randomization (MR) analysis to evaluate causal relationships between liability to COVID-19 (and severe/critical infection) and a wide range of neuropsychiatric disorders or traits. We employed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…While this is an observational study, it is interesting to note that Mendelian randomization studies, which are less prone to confounding, have also shown that COVID-19 may be a causal risk factor for various cardiometabolic and neuropsychiatric disorders 44,45 .…”
Section: Interpretation Of Findings In the Context Of Previous Studiesmentioning
confidence: 99%
“…While this is an observational study, it is interesting to note that Mendelian randomization studies, which are less prone to confounding, have also shown that COVID-19 may be a causal risk factor for various cardiometabolic and neuropsychiatric disorders 44,45 .…”
Section: Interpretation Of Findings In the Context Of Previous Studiesmentioning
confidence: 99%